Exploring the nexus between appropriability and productivity in highly innovative and globalised companies - Sara Amoroso; Randolph Bruno; Laura Magazzini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
This paper identifies the dichotomous role (bright and dark sides) of Intellectual Property Rights (IPR) protection on labor productivity among highly innovative globalised firms. The role of appropriability conditions-such as IPR protection- as "Schumpeterian" incentive to innovation has been largely explored in the em- pirical literature. In this paper, we contribute to this strand explore the role of appropriability conditions on firm labor productivity under different configurations of R&D activities in highly globalized companies. In line with the literature, we show that labor, capital and R&D investments lead to productivity gains, and that the strength of the patent system the firm is embedded into is positively linked to the firm's labor productivity too. We call this the 'bright side' of IPR. However, stronger intellectual property rights might have a detrimental effect on the R&D re- turns, which appear to be maximized around the median level of IPR protection. In other words, too much protection might actually reduce R&D returns, again in line with the "Schumpeterian prediction". Then, we call this the 'dark side' of IPR. To our knowledge, this is the first paper highlighting such dichotomy (bright and dark sides of IPR) on a purpose-built high-quality database of globalized firms, which tend to be the most innovative firms in the world.
Keywords: C23; O34; 330; panel data; appropriability; productivity